Plant-derived natural products against hepatocellular carcinoma: chemical diversity, mechanisms of action, and organ-based classification - Nourhan Hisham Shady; Aliaa Gamal; Asmaa Emad Fekry; Amna Mahmoud Sayed; Zaki Ebrahim Afify; Ziad Abdellah Mohamed; Ingy M. Hashad; Mohammed I. Rushdi; Ahmed Zayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2026)

Integrating Litopenaeus vannamei into Dicentrarchus labrax hypersaline earthen ponds improves productivity and farm profitability: evaluating shrimp performance and economic viability under the effect of bile acid supplementation - Tamer El-Sayed Ali; Ashraf I. G. Elhetawy; Eenas Abdullah Hamad Ateeyah; Ahmed M. F. Sultan; Mohamed M. Zayed; Mohamed M. Abdel-Rahim (Aquaculture International, 2026)

Exploring the effect of bronopol exposure length on the suppression of Aeromonas hydrophila infection in nile tilapia (Oreochromis niloticus L.) - Zizy I. Elbialy; Eman M. Moustafa; Amira A. Omar; Abdallah S. Salah; Ahmed Elsheshtawy; Mohammed M. Zayed; Marwa F. Abdel-Kader; Hani Y. Labib; Hossam I. Kadira; Dina B. Barsem; Ahmed E. Elshafey; Sayed M. Aboleila; et al. (Veterinary Research Communications, 2026)

Optimized TiO₂/GO/PES Forward Osmosis Membrane for Wastewater Reclamation Using Qarun Lake Brine as a Draw Solution - Mervat Nasr; Mohamed Shaban; Mohamed G. M. Kordy; Mohamed Zayed; Ashour M. Ahmed; Sameerah I. Al-Saeedi; Hind Alshaikh; Sahar S. Ali; Hany Hamdy; Hanafy M. Abd El-Salam (Water, Air, & Soil Pollution, 2025)

Integrated aquaculture of whiteleg shrimp Litopenaeus vannamei and European seabass Dicentrarchus labrax: impacts on performance, welfare, blood physiological response, carcass traits, productivity, and farm profitability - Ashraf.I. G. Elhetawy; Abdallah Tageldein Mansour; Ayman M. Lotfy; Ahmed. I. A. Mansour; Shimaa A. Shahin; Mohamed M. Zayed; Ghada R. Sallam; Mohamed M. Abdel-Rahim (Aquaculture International, 2025)
Seabass farmers suffer from a long-lasting production period of at least 18 months, causing a long-term gap in financial income and payback. This study investigated the integration of Litopenaeus vannamei with Dicentrarchus labrax aquaculture allowing seabass farmers to earn a consistent income 2–3 times a year. Six treatments (seabass alone “control group,” seabass with 5, 10, 15, 20, and 25 shrimp in the fish tanks) were tested in triplicate and expressed as S0, S5, S10, S15, S20, and S25, respectively. Seabass was housed at a standardized density (12 fish/tank, each 3500 L water). Fifteen hapas (each 1 m × 1 m, 700 L water volume) were installed in 15 rearing tanks to hold the experimental shrimp, occupying 20% of the tank’s water volume. Both fish and shrimp received specialized diets during the 90-day experiment. The findings indicated that increasing shrimp density by more than 15 juveniles/hapa significantly ( P 3 ) and decreased growth performance and feed efficacy in seabass and shrimp. Moreover, increasing the shrimp density noticeably ( P P 2 (S15 group). Furthermore, integrating shrimp in seabass tanks improved gross income, net profit, benefit–cost ratio, and payback period of seabass. The recommended shrimp density when integrated with seabass using a flow-through system is 15 pcs/m 2 .

Design, synthesis and biological evaluation of benzimidazole/bis-imine derivatives as glyoxalase I inhibitors - Buthina A. Al-Oudat; Suaad A. Audat; Nizar A. Al-Shar’i; Qosay A. Al-Balas; Hana’a M. Jaradat; Lara Fakhouri; Aref L. Zayed (Medicinal Chemistry Research, 2025)

Structural optimization and biological evaluation of quinoline/naphthalene-based glyoxalase-I inhibitors as anti-cancer candidates - Buthina A. Al-Oudat; Bushra S. Abu Al fool; Suaad A. Audat; Nizar A. Al-Shar’i; Qosay A. Al-Balas; Aref Zayed; Amanda Bryant-Friedrich (Medicinal Chemistry Research, 2024)

Virus ecology and 7‐year temporal dynamics across a permafrost thaw gradient - Christine L. Sun; Akbar Adjie Pratama; Maria Consuelo Gazitúa; Dylan Cronin; Bridget B. McGivern; James M. Wainaina; Dean R. Vik; Ahmed A. Zayed; Benjamin Bolduc; Kelly C. Wrighton; Virginia I. Rich; Matthew B. Sullivan (Environmental Microbiology, 2024)
Soil microorganisms are pivotal in the global carbon cycle, but the viruses that affect them and their impact on ecosystems are less understood. In this study, we explored the diversity, dynamics, and ecology of soil viruses through 379 metagenomes collected annually from 2010 to 2017. These samples spanned the seasonally thawed active layer of a permafrost thaw gradient, which included palsa, bog, and fen habitats. We identified 5051 virus operational taxonomic units (vOTUs), doubling the known viruses for this site. These vOTUs were largely ephemeral within habitats, suggesting a turnover at the vOTU level from year to year. While the diversity varied by thaw stage and depth‐related patterns were specific to each habitat, the virus communities did not significantly change over time. The abundance ratios of virus to host at the phylum level did not show consistent trends across the thaw gradient, depth, or time. To assess potential ecosystem impacts, we predicted hosts in silico and found viruses linked to microbial lineages involved in the carbon cycle, such as methanotrophy and methanogenesis. This included the identification of viruses of Candidatus Methanoflorens, a significant global methane contributor. We also detected a variety of potential auxiliary metabolic genes, including 24 carbon‐degrading glycoside hydrolases, six of which are uniquely terrestrial. In conclusion, these long‐term observations enhance our understanding of soil viruses in the context of climate‐relevant processes and provide opportunities to explore their role in terrestrial carbon cycling.

Chlorella vulgaris extract conjugated magnetic iron nanoparticles in nile tilapia (Oreochromis niloticus): Growth promoting, immunostimulant and antioxidant role and combating against the synergistic infection with Ichthyophthirius multifiliis and Aeromonas hydrophila - Doaa Ibrahim; Mona Mohammed I. Abdel Rahman; Amany M. Abd El-Ghany; Eman A. A. Hassanen; Omar A. Al-Jabr; Reham A. Abd El-Wahab; Shimaa zayed; Mona Abd El khalek Salem; Shimaa Nabil El_Tahawy; Wessam Youssef; Heba A. Tolba; Rehab E. Dawod; et al. (Fish & Shellfish Immunology, 2024)

Sequential deuteric and hydrothermal alterations in the Late Neoproterozoic Um Naggat rare metal-bearing granite, Central Eastern Desert, Egypt - I. Gamal-Adeen; M.G. Shahien; A.M. Zayed; B.R. Bakhit; I.V. Sanislav; A.S.A.A. Abu Sharib (Journal of African Earth Sciences, 2023)

Litoarbolide A: an undescribed sesquiterpenoid from the Red Sea soft coral Litophyton arboreum with an in vitro anti-malarial activity evaluation - Mohammed M. A. Ahmed; Ehab A. Ragab; Ahmed Zayed; Elsayed M. El-Ghaly; Said K. Ismail; Shabana I. Khan; Zulfiqar Ali; Amar G. Chittiboyina; Ikhlas A. Khan (Natural Product Research, 2023)

A hybrid system coupling spiral type solar photovoltaic thermal collector and electrocatalytic hydrogen production cell: Experimental investigation and numerical modeling - Mohamed I. El-Hadary; S. Senthilraja; Mohamed E. Zayed (Process Safety and Environmental Protection, 2023)

The RNA virosphere: How big and diverse is it? - Guillermo Dominguez‐Huerta; James M. Wainaina; Ahmed A. Zayed; Alexander I. Culley; Jens H. Kuhn; Matthew B. Sullivan (Environmental Microbiology, 2023)

Dietary Lactobacillus acidophilus ATCC 4356 Relieves the Impacts of Aflatoxin B1 Toxicity on the Growth Performance, Hepatorenal Functions, and Antioxidative Capacity of Thinlip Grey Mullet (Liza ramada) (Risso 1826) - Malik M. Khalafalla; Nahed F. A. Zayed; Asem A. Amer; Ali A. Soliman; Amr I. Zaineldin; Mahmoud S. Gewaily; Aziza M. Hassan; Hien Van Doan; Wanaporn Tapingkae; Mahmoud A. O. Dawood (Probiotics and Antimicrobial Proteins, 2022)

The role of the pituitary-ovarian axis in the termination of early pregnancy in rabbits treated with ethinyl-oestradiol - M. A. Attia; H. F. P. Joosten; I. Zayed; A. Hoekstra (Archives of Toxicology, 1980)

Cytological study on the anterior pituitary of beagle bitches treated subcutaneously with progesterone for 13 weeks - M. A. Attia; I. Zayed (Archives of Toxicology, 1978)

On the fungicidal properties of thioaceto-hydroxamic acids and related compounds - I. Y. Mostafa; S. M. A. D. Zayed; M. Farghaly (Archives of Microbiology, 1967)

Organische P-haltige Insecticide im Stoffwechsel - S. M. A. D. Zayed; I. Y. Mostafa; A. Hassan (Archives of Microbiology, 1965)